a) [tex] \frac{5 \sqrt{24} }{ \sqrt{3} } - \frac{7 \sqrt{24} }{ \sqrt{2} } - \frac{5 \sqrt{54} }{ \sqrt{3} } + \frac{6 \sqrt{54} }{ \sqrt{2} } - \sqrt{48} =
= [tex] \frac{10 \sqrt{6} }{ \sqrt{3} } - \frac{14 \sqrt{6} }{ \sqrt{2} } - \frac{15 \sqrt{6} }{ \sqrt{3} } + \frac{18 \sqrt{6} }{ \sqrt{2} } - 4 \sqrt{3} =
=[tex] \frac{10 \sqrt{18} }{3} - \frac{14 \sqrt{12} }{2} - \frac{15 \sqrt{18} }{3} + \frac{18 \sqrt{12} }{2} - 4 \sqrt{3} =
= [tex]- \frac{15 \sqrt{2} }{3} + \frac{8 \sqrt{2} }{2} - 4 \sqrt{3} =
= [tex] \frac{30 \sqrt{2} }{6} + \frac{24 \sqrt{2} }{6} - \frac{24 \sqrt{3} }{6} =
= [tex] \frac{54 \sqrt{2} - 24 \sqrt{3} } {6} =
= [tex]9 \sqrt{2} - 4 \sqrt{3} [/tex]